DEFISIT DEMOKRASI INTERNAL PARTAI DALAM PROSES REKRUTMEN CALON KEPALA DAERAH PADA PILKADA TANGERANG SELATAN 2020 (STUDI KASUS DPD PARTAI GOLKAR KOTA TANGERANG SELATAN) - Mohammad Irsyaad Rizky Ghozali (2024)
Political parties which have a recruitment function by nominating someone are not fully carried out properly by political parties. In practice, now political parties in recruiting regional head candidates prefer candidate popularity and a centralized pattern with the decision to be in the DPP. Golkar Party is one of the parties participating in the 2020 simultaneous regional elections, one of which is in South Tangerang City. This research tries to reveal the mechanisms and steps involved in the recruitment process for regional head candidates, including how decision making is carried out in selecting candidates to be nominated. The concept used is political recruitment to help explain the context of recruitment of regional head candidates and internal party democracy to help analyze how exclusive or inclusive the regional head candidate recruitment process is carried out by the Golkar Party so that it has an impact on democracy within the party. The method used is descriptive qualitative using primary data sources and secondary data. This research uses data collection techniques through interviews and literature studies in the form of books, news, audiovisuals and previous research journals that are relevant to this research. The results of the research show's that the recruitment process for regional head candidates by Golkar Party in the South Tangerang Regional Election tends to be exclusive, with the presence of nomination committees, from regional to national level, and recruitment decisions and strategies are determined more by elites at the Regional Representative Council (DPD) level 1&2, and national. Apart from that, there is a tendency for the recruitment process to run exclusively in the candidacy process by prioritizing party members with additional requirements, such as popularity and electability, as well as capital owned. In addition, there is a tendency for selection methods to be centralized at the national level through DPP Golkar Party, with limited involvement from the local level, especially the South Tangerang City DPD. Ultimately, the selected candidates are not chosen based on internal party voting, but through an appointment mechanism.